So mote it be …. Issue 2 (17th May 2012) - Phillips, Mike
'So mote it be …' describes a trinity of artworks by Mike Phillips that explore the delicate relationship we have with the extremes of our perception. These data-driven sonifications and visualizations play with the atomic forces that bind the material world as measured through the atomic force microscope (AFM). The works try and locate the trauma of seeing things that are invisible and beyond the resolution of the human eye to a history of cultural experience that similarly tries to see things that might ordinarily have been perceived as occult or at the very least the product of Hollywood.